Comparison of transoral power-assisted endoscopic adenoidectomy to curettage adenoidectomy - Öztürk, Özmen; Polat, Şenol (Springer, 2012)
Introduction: The aim of this prospective and randomized study was to compare patients who underwent curettage adenoidectomy (CA) or transoral power-assisted endoscopic adenoidectomy (PAEA) performed as isolated procedures by a single surgeon over a period of 7 years. The success of an adenoidectomy has been evaluated by assessing the amount of reduction in the adenoid size and the symptomatic improvement at the sixth postoperative month. Methods: Patients' nasal airway obstruction was graded by the parents of the patient on a visual analog scale (VAS), with a range from 0 to 10, with grade 10 representing total obstruction. The ratio of the choanal opening obstructed by an adenoid mass was measured and expressed in percentages as representative of the adenoid size. Preoperative and 6-month postoperative adenoid sizes were compared. Results: Fifty-three patients (CA group 27 patients/PAEA group 26 patients) completed the study. In the CA group, VAS score improved from the preoperative score of 8.63 ± 0.88 to the 6-month score of 2.22 ± 1.01 (P lt; 0.0001); and in the PAEA group, the preoperative VAS score of 8.69 ± 0.84 improved to 2.08 ± 1.05 in the same period (P lt; 0.0001). No statistical significance was found when VAS score improvements were compared (P = 0.4569). The average ratio of choanal opening obstructed by an adenoid mass improved from the preoperative ratio of 89.41% ± 6.48% to the 6-month ratio of 7.85% ± 2.28% in the CA group; and the preoperative ratio of 90.19% ± 6.95% in the PAEA group improved to 3.65% ± 1.38% after 6 months. The reduction of adenoid size was significantly superior in PAEA than CA (P lt; 0.0001). The operative time in PAEA was significantly shorter than that in CA (P lt; 0.0001). Conclusion: Although symptomatic improvement at the 6-month follow-up is statistically indifferent, PAEA has been shown to be superior to CA with its superior performance in providing a near-total elimination of the adenoid mass in a shorter operating time.
Keywords: Adenoid; Adenoidectomy; Complications; Curettage; Endoscopic surgical procedure